FEATURES OF INDUSTRIAL HYDROGEOLOGICAL RESEARCHES AT WEST-STAROVIRIVSKE GAS-CONDENSATE FIELD WITH ASPECTS OF FIELD ECOLOGIZATION - Хорішко, Валерій Вікторович; Самойлов, Віталій Вікторович; Бортняк, Олена Михайлівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The paper refers to the problem of drowning of the gas-condensate fields. The features of negative effect on the environment caused by the technological methods of intensive arrival control of field water to the near bottomhole zone of wells in operation are presented as well as the necessity and expediency of using geophysical and geochemical methods to control drowning or the reservoirs were proved. The results of geological studies on drowning of wells at the West-Starovirivske gas-condensate field are presented together with the quantitative and qualitative analysis of associated water, which is removed in case when several wells have common entry to the facility of gas complex treatment (FGCT) and there is no possibility to perform each study separately. In order to specify a group of drowning wells, the "Pearson’s square" method was used to determine the water-cut for each group of wells. Industrial data on water factors of wells, obtained directly at FGCT, as well as data obtained during hydrogeological studies with small separation plant were analyzed.